Sveobuhvatni pristup NATO-a sajber odbrani (Kriminalističke teme, 2019)
Inspiracija za rad i problem (i) koji se radom oslovljava (ju): U eri dominacije informacione tehnologije, sajber prostor je postao značajan sigurnosni problem za vlade koje su prisiljene poduzeti dodatne mjere za poboljšanje sajber sigurnosti.Ciljevi rada (naučni i/ili društveni): U situaciji povećane upotrebe informacionih tehnologija u današnjem globaliziranom svijetu, cyber odbrana postaje veliki prioritet ne samo za pojedine zemlje, već i za njihove kolektivne mehanizme.Metodologija/Dizajn: Ovaj rad bavi se problemima NATO kibernetičke odbrane i sajber bezbjednosti i mogućim poraznim efektima i posljedicama cyber napada. U tom cilju autori će koristiti dostupnu stručnu literaturu i online publikacije na ovu temu, na kojima će se primijeniti kvalitativna analiza sadržaja. Teret istraživanja bit će na strateškim i operativnim mjerama sigurnosti i obrane Saveza, jer postoji ograničena dostupnost informacija o mjerama taktičkog nivoa koje su povjerljive.Ograničenja istraživanja/rada: Autori rada nastoje da razrade koordinirani i sveobuhvatni pristup NATO-a u postizanju efektivne sajber odbrane i sigurnosti komunikacionih i informacionih sistema za članice Saveza i njihove partnere.Rezultati/Nalazi: Pitanja koja se pojavljuju su: koliko NATO savez ozbiljno razmatra rizike cyber napada, na koji način to odražava promjene u politici odbrane i strateškim konceptima Alijanse, koji je pristup rješavanju ovog novog sigurnosnog izazova i koje su obaveze na nivou Saveza?!Generalni zaključak: Odgovor je da se fokus NATO-a u narednoj deceniji mora odnositi na razvoj sajber-moći.Opravdanost istraživanja/rada: Tehnologija je u srcu naših čvrsto povezanih društava. Oslanjanje modernih društava na informacionih tehnologija podrazumijeva očigledne bezbjednosne probleme. Cyber prijetnje i napadi postaju sve češći, sofisticiraniji i štetniji. Čak i vojske i službe bezbjednosti koje se u velikoj mjeri oslanjaju na sajber prostor za obavljanje svojih misija nisu imune na takve napade.NATO's Comprehensive Approach to Cyber DefenseReason for writing and research problem (s): In the era of domination of information technology, cyber space has become a significant security issue for governments that are forced to take additional measures to enhance cyber security.Aims of the paper (scientific and/or social): In a situation of increased use of information technology in today's globalized world, cyber defense is becoming a high priority not only for individual countries, but also for their collective mechanisms.Methodology/Design: This paper addresses the problems of NATO cyber defense and cyber security and the possible defeating effects and consequences of cyber-attacks. To this end, the authors will use the available expert literature and online publications on this subject, on which a qualitative analysis of the content will be applied.Research/Paper limitation: The authors of the paper make an attempt to elaborate NA-TO's coordinated and comprehensive approach in achieving effective cyber defense and security of communication and information systems for Alliance members and their Partners.Results/Findings: The burden of the research will be on the strategic and operational security and defense measures of the Alliance because there is limited availability of information on tactical level measures that are kept confidential. The issues that arise are: how much does the NATO Alliance seriously consider the risks of cyber-attacks, in which way it reflects the changes in the defense policy and strategic concepts of the Alliance, what is the approach to tackling this new security challenge and what are the commitments at the level the alliance to further improve security in cyber space?!General Conclusion: The answer is that NATO's focus in the next decade must be on the development of cyber power.Research/Paper Validity: Technology is at the heart of our tightly knit societies. Modern societies' reliance on information technology implies obvious security problems. Cyber threats and attacks are becoming more common, sophisticated and harmful. Even the military and security services that rely heavily on cyberspace to carry out their missions are not immune to such attacks.